2002
DOI: 10.1007/s10265-002-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of aminoaldehyde dehydrogenase from Avena sativa

Abstract: NAD-dependent aminoaldehyde dehydrogenase (AMADH, EC 1.2.1.-) from Avena shoots was purified by DEAE Sephacel, hydroxyapatite, 5'-AMP Sepharose 4B, Mono Q, and TSK-GEL column chromatographies to homogeneity by the criterion of native PAGE. SDS-PAGE yielded a single band at a molecular mass of 55 kDa. IEF studies showed a band with a p I value of 5.3. In contrast to AMADHs from other species, the TSK-GEL chromatography showed that AvenaAMADH exists as a monomer in the native state. The purified enzyme catalyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…The BADH enzymes in sugar beet (Beta vulgaris), spinach (Spinacia oleracea), and oat (Avena sativa) all showed broad substrate specificities, catalyzing the oxidation not only of betaine aldehyde (Bet-ald) but also of other v-aminoaldehydes (Trossat et al, 1997;Incharoensakdi et al, 2000;Livingstone et al, 2003). To elucidate the role of BADH2 in 2AP biosynthesis, we characterized its aldehyde dehydrogenase activity as well as its substrate specificity.…”
Section: Badh2 Exhibits Aldehyde Dehydrogenase Activitymentioning
confidence: 99%
“…The BADH enzymes in sugar beet (Beta vulgaris), spinach (Spinacia oleracea), and oat (Avena sativa) all showed broad substrate specificities, catalyzing the oxidation not only of betaine aldehyde (Bet-ald) but also of other v-aminoaldehydes (Trossat et al, 1997;Incharoensakdi et al, 2000;Livingstone et al, 2003). To elucidate the role of BADH2 in 2AP biosynthesis, we characterized its aldehyde dehydrogenase activity as well as its substrate specificity.…”
Section: Badh2 Exhibits Aldehyde Dehydrogenase Activitymentioning
confidence: 99%
“…Optimum activity of BAD1 and BAD2 towards bet-ald was found to be at pH 9.5 and pH 10 respectively. High pH optima have been reported for many AAD and BAD enzymes including BAD from oats (Livingstone et al 2003), Zoysia tenuifolia (Oishi and Ebina 2005) and AAD from pea (Sebela et al 2000). Both rice BAD1 and BAD2 are believed to be directed to the peroxisome (Nakamura et al 1997;Bradbury et al 2005a).…”
Section: Enzyme Half Life and Ph Optimamentioning
confidence: 99%
“…Many recent studies have found plant BADs are capable of metabolising a range of substrates including omega-aminoaldehydes, often more efficiently than bet-ald (Trossat et al 1997;Incharoensakdi et al 2000;Livingstone et al 2003;Oishi and Ebina 2005), while others report enzymes with aminoaldehyde dehydrogenase (AAD) activity that have high homology to BADs but no affinity for bet-ald (Sebela et al 2000), leading to the suggestion BADs and AADs are the same enzyme and should be reclassified as such (Sebela et al 2000;Livingstone et al 2003;Reumann 2004).…”
Section: Introductionmentioning
confidence: 99%
“…20) Betaine aldehyde dehydrogenase of E. coli, 31) Xanthomonas translucens, 32) and Arthrobacter globiformis 33) is a homotetramer with 50-55 kDa subunits. On the other hand, betaine aldehyde from P. aeruginosa 34) and plants [35][36][37] is a homodimer of 61-63 kDa. 4-Aminobutyraldehyde dehydrogenases (EC.1.2.1.19), which have been purified from Pseudomonas, 38) E. coli, 39,40) and mammalians, [41][42][43] also have been reported to act as dimers, 40,43) trimers, 38) or tetramers.…”
Section: Reagentmentioning
confidence: 99%